Assessment of voltage and current quality indices of grid connected solar PV plants against international - Ramachandaramurthy, V.K.; Yong, J.Y.; Tan, K.M.; Pouryekta, A.; Jayasinghe, D.H.G.A.E.; Ekanayake, J.B. (IEEE, 2019)
The renewable energy based power generation is increasingly gaining attention with the technological advances and global climatic concerns. Among different type of the renewable energy sources solar photovoltaic (PV) become the most prominent renewable energy source. As solar PV is connected to the all voltage levels in a power system, the intermittency and variability of solar PV output may raise the issues in stability of the system. It was identified that in order to minimize the impact of intermittent distributed generators like solar PV, they should comply with distribution codes/guidelines which are introduced by utilities/standardization bodies. However with the penetration level of PV is increasing utilities have fears about adequacy of distribution codes/guidelines. This research communication presents a performance assessment of grid connected solar PV plants against a number of distribution codes/guidelines using the real time measurements of five sites in Malaysia. The measurement of RMS voltage, Total Harmonic Voltage Distortion, Total Harmonic Current Distortion, Voltage Unbalance, and Voltage Flicker of the grid connected PV plants were taken into consideration. The results shows that PV systems considered comply with all the essential requirements of the international standards.
Keywords: Solar power.; Distribution codes.; Test results; Compliance to international standards